2014
DOI: 10.1371/journal.pone.0105400
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Differentially Expressed Proteins Induced by Hydrogen Sulfide in Spinacia oleracea Leaves

Abstract: Hydrogen sulfide (H2S), as a potential gaseous messenger molecule, has been suggested to play important roles in a wide range of physiological processes in plants. The aim of present study was to investigate which set of proteins is involved in H2S-regulated metabolism or signaling pathways. Spinacia oleracea seedlings were treated with 100 µM NaHS, a donor of H2S. Changes in protein expression profiles were analyzed by 2-D gel electrophoresis coupled with MALDI-TOF MS. Over 1000 protein spots were reproducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Sulfur has unique chemical properties because it occurs in a wide range of oxidation states (from −2 to +6) in different compounds, and hence sulfur-derived metabolites are major participants of redox metabolism and post-translational modifications as well as of detoxification processes. Two RSSs, hydrogen sulfide and sodium sulfite have been recently shown to play important roles in plant disease resistance [7,[199][200][201][202][203].…”
Section: Reactive Sulfur Species (Rss)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur has unique chemical properties because it occurs in a wide range of oxidation states (from −2 to +6) in different compounds, and hence sulfur-derived metabolites are major participants of redox metabolism and post-translational modifications as well as of detoxification processes. Two RSSs, hydrogen sulfide and sodium sulfite have been recently shown to play important roles in plant disease resistance [7,[199][200][201][202][203].…”
Section: Reactive Sulfur Species (Rss)mentioning
confidence: 99%
“…Recent studies have suggested that not H 2 S, but rather H 2 S donor sulfane sulfur compounds act as signaling molecules and are responsible for the biological activities of some RSS [207]. H 2 S influences several physiological processes, it promotes root organogenesis, seed germination, lateral root formation and enhances photosynthesis [201,203]. H 2 S treatment of plants confers protective roles in responses to heat, drought, salt, osmotic, and freezing stresses [203,205].…”
Section: Reactive Sulfur Species (Rss)mentioning
confidence: 99%
“…Endogenous H 2 S content was determined according to the procedure of Zhang et al [62], and the method of Chen et al was employed to determine the dry weight [63].…”
Section: Determination Of Dry Weight and The Content Of Endogenous H 2 Smentioning
confidence: 99%
“…However, it has recently been found to have properties similar to those of multifunctional signaling molecules (NO and H 2 O 2 ) (Lisjak et al ; Gotor et al ; Hancock and Whiteman ; Li et al ; Yamasaki and Cohen ; Filipovic and Jovanovic ). As with NO and H 2 O 2, exogenous applications of H 2 S in plants have been shown to counteract the toxic effects of stresses, such as heavy metal and salinity (Zhang et al ; Chen et al , , ; Ali et al ; Bharwana et al ; Kharbech et al ; Corpas et al ). In plant systems, several enzymes are capable of generating H 2 S, which is part of the cysteine (Cys) metabolism.…”
Section: Introductionmentioning
confidence: 99%